Optimal Inequalities for Generalized Logarithmic, Arithmetic, and Geometric Means - Chu Yu-Ming (Journal of Inequalities and Applications, 2010)
For , the generalized logarithmic mean , arithmetic mean , and geometric mean of two positive numbers and are defined by , for , , for , , and , , for , and , , for , and , , and , respectively. In this paper, we find the greatest value (or least value , resp.) such that the inequality (or , resp.) holds for (or , resp.) and all with .